Cognitive and Experiential Processes in Economic Expectations and Decision-Making - Yildirim, Eren; Uzunoz, Meral (ISTANBUL UNIV, 2021)
In the process of forming expectations and decision-making, how brain processes internal and external information and experiences and the factors are affecting these processes are an important discussion. In this context, the relationship between an agent's emotions and rational reasoning ability and that between expectation formation and decision-making process are important. In the mainstream economic literature, expectation and decision-making theories are formed by perspectives reliant on the cognitive aspects of these processes. However, such perspectives do not explain the relationship of emotions and affect with intuitive and experiential systems. In this respect, the relationship between the experiential system and the rational system must be analyzed. They are expressed in metaphors of mind and emotion in psychology, cognitive neuroscience, and behavioral economics literature, which should be included more intensively in economic methodology. The dual-process theories applied in the field of psychology work on the information processing and thinking systems of an individual. The distinction and interdependence between the rational reasoning of the brain and the experiential process of information processing, especially those of the dual-process theories, show that the framework of economic expectations and established theories of decision-making is insufficient to understand the process of forming those processes. To overcome this important deficiency in economic literature, it is concluded with the help of related literature that emotions affect the expectation and decision-making formation and that the experiential process in the brain works in a manner that works together collaboration with the rational system.
Keywords: Expectations; Dual-Process Theories; Irrationality. Emotions; Affect; Government & Law